The Relationship Between Work Motivation and Employee Performance in employees of companies from Jakarta that are mainly engaged in companies in the Field of Livestock Breeding, Feed Production, and Processing of Livestock Products: Hubungan Antara Motivasi Kerja dengan Kinerja Karyawan pada karyawan perusahaan asal Jakarta yang terutama bergerak Perusahaan di Bidang Pembibitan Ternak, Produksi Pakan, dan Pengolahan Hasil Peternakan - Santoso, Nurvian Haris; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this research is to work motivation and employee performance at PT. Japfa Comfeed Indonesia Tbk. Surabaya This research is aquantitative research with a correlational approach. The population in this study were all employees of PT. Japfa Comfeed Indonesia Tbk. Unit Surabaya, which has 247 employees. The sample of this study consisted of 153 employees using simple random sampling technique (ɑ=0.922) The data analysis method used was Pearson's Product Moment correlation using SPSS 22.0 The results of data analysis in this study showed a correlation coefficient (rxy) of 0.559, indicating a significance of 0.000< 0. This is PT. Japfa Comfeed Indonesia Tbk. Unit Surabaya. The effect of work motivation on employee performance is 31.2% in this study